Analisis Pertumbuhan Ekonomi, Kurs Dollar Dan 7-Day Reverse Repo Rate Terhadap IHSG - Heri Sasono; M. Nuruzzaman (Universitas 45 Surabaya, 2024)
The Composite Stock Price Index (IHSG) is a reflection of a country's economic progress. The main objective of this research is to analyze the influence of Macro Variables on the Composite Stock Price Index (IHSG). The macro variables used in this research are Economic Growth, Dollar Exchange Rate and SBI (7-Day Reverse Repo Rate). The years used as research samples are 10 years, namely from 2013 to 2022. Research analysis uses linear regression analysis multiple, t test, F test, coefficient of determination test using SPSS Version 26 software. Research conclusions: Economic growth and the dollar exchange rate do not have a significant effect on the IHSG, while SBI has a significant effect on the IHSG. Then simultaneously Economic Growth, Dollar Exchange Rate and SBI have a significant effect on IHSG